A solar fed BLDC motor drive for mixer grinder using a buck converter - Deekshitha S. Nayak; R. Shivarudraswamy (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In large and small scale applications, different kinds of variable speed driving systems can be found. For saving the energy consumption of these devices, eco-friendly electronics are used, which lead to the development of the Brushless DC motor (BLDC). Its higher power density, higher efficiency, higher torque at low speed, and low maintenance enhances the use of a BLDC motor. The existing mixer grinder consists of the universal motor, which operates in alternating current supply due to high starting torque characteristics and simple controlling of the speed. The absence of brushes and the reduction of noise in the BLDC extends its life and makes it ideal in a mixer grinder. A solar-powered BLDC motor drive for a mixer grinder is presented in this paper. A DC-DC buck converter is utilized to operate the PV (photovoltaic) array at its maximum power. The proposed hysteresis current control BLDC system has been developed in the MATLAB. The commercially available mixer grinder is presented along with the proposed simulated system for performance comparison. It can be concluded that at the no load condition, the efficiency of the experimental existing mixer grinder is 51.03% and simulated proposed system is 81.25% and at load condition, the efficiency of the experimental mixer grinder is 49.32% and simulated system is 79.85%.